A comprehensive criteria-based multi-attribute decision-making model for rehabilitation of water distribution systems. Issue 6 (3rd June 2018) - Salehi, Sattar; Jalili Ghazizadeh, Mohammadreza; Tabesh, Massoud
Abstract: The main objective of this work is to develop a comprehensive criteria-based multi-attribute decision-making model to plan the rehabilitation of water networks. Among the main features of this model is the capability to simultaneously analyse comprehensive criteria for the rehabilitation of water networks; where there is a significant uncertainty within the operational data. In this model, which is called as WDSR model, using a fuzzy TOPSIS technique, it is possible to adjust the criteria based on the local conditions, and to weight them based on the group decision-making of experts. In this paper, using the WDSR model, the rehabilitation plan of the 'Anytown' water network is prioritised through two methods. The first method uses a predefined template of WDSR, and the second uses a local template based on the conditions within the study area. The obtained results show the potential of the WDSR in the rehabilitation planning of water networks, where is encountered with numerous criteria, a significant uncertainty in the recorded data and hesitation in group decision-making of experts. It was found that, for rehabilitation of network zones, predefined template of WDSR is preferred, while for pipe rehabilitation, it is essential to use local template layer.